Industrial Relations Dispute Settlement of PT Samindo Utama Kaltim by the Regional Office of Manpower and Transmigration Department of the Paser Regency, East Kalimantan - Ariq Shalahudin Al Fayed (Universitas Muhammadiyah Yogyakarta, 2022)
East Kalimantan is an area in Indonesia rich in natural resources, and it undoubtedly has attracted many foreign companies to extract them. Certainly, the numerous companies extracting natural resources have led to the emergence of disputes. This study employed a qualitative method with data analysis obtained from the Regional Office of Manpower and Transmigration Department of the Paser Regency regarding the industrial relation disputes settlement in multinational companies. This working report explained the forms of industrial relations dispute settlement of a multinational company named PT Samindo Utama Kaltim in Paser Regency, East Kalimantan, by the Regional Office of Manpower and Transmigration Department and how the International Labor Organization (ILO) policies were related to the company’s disputes. It was revealed that the problem-solving carried out by PT Samindo Utama Kaltim followed the ILO policies.